Exploratory study of long‐term health‐related quality of life in patients with surgically treated primary parotid gland cancer. Issue 1 (22nd May 2015) - Stenner, Markus; Beenen, Franziska; Hahn, Moritz; Koopmann, Mario; Weiss, Daniel; Hüttenbrink, Karl‐Bernd
Abstract: Background: Health‐related quality of life (HRQOL) has received more and more attention as an outcome in cancer therapy. In this exploratory study, we assessed the long‐term HRQOL among 77 surgically treated patients with parotid gland cancer. Methods: The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Core 30‐questions (EORTC‐QLQ‐C30) and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Core 30 Head and Neck 35‐questions (EORTC‐QLQ‐C30‐H&N35) questionnaires were used in a cross‐sectional design. The mean time‐lag between initial diagnosis and completion of the questionnaire was 89.7 months. Results: The HRQOL significantly increased with the time‐lag to surgery and decreased with the patients' age. Factors with clinically significant effects in several areas of long‐term HRQOL (ie, more than 4 scores) were age, type of neck dissection, preoperative facial nerve palsy, and postoperative radiation therapy. Conclusion: In parotid gland cancer surgery, factors, such as sex, age, type of surgery, facial nerve palsy, and radiation therapy, seem to be associated with clinically meaningful differences in long‐term HRQOL scores. © 2015 Wiley Periodicals, Inc. Head Neck 38: 111–117, 2016